2010
DOI: 10.1073/pnas.0912701107
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a microRNA signature of renal ischemia reperfusion injury

Abstract: Renal ischemia reperfusion injury (IRI) is associated with significant morbidity and mortality. Given the importance of microRNAs (miRNAs) in regulating gene expression, we examined expression profiles of miRNAs following renal IRI. Global miRNA expression profiling on samples prepared from the kidneys of C57BL/6 mice that underwent unilateral warm ischemia revealed nine miRNAs (miR-21, miR-20a, miR-146a, miR-199a-3p, miR-214, miR-192, miR-187, miR-805, and miR-194) that are differentially expressed following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
348
3
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(375 citation statements)
references
References 40 publications
18
348
3
6
Order By: Relevance
“…Ischemia markedly initiates injury of both the renal tubular epithelium and renal microvasculature, which is exacerbated upon reperfusion by an increase in oxidative stress, infl ammation, apoptosis, and necrosis (Bonventre and Weinberg, 2003;Devarajan, 2006). MiR-21 down-regulated apoptosis and necrosis of renal TECs, which promoted cellular proliferation and played a protective role in the response to stress and infl ammation in renal IRI (Lindsay, 2008;Thum et al, 2008a;Godwin et al, 2010). As shown in a previous animal study, knockdown of miR-21 increased cell death.…”
Section: Mir-21 and Ischemia Reperfusion Injurymentioning
confidence: 68%
See 2 more Smart Citations
“…Ischemia markedly initiates injury of both the renal tubular epithelium and renal microvasculature, which is exacerbated upon reperfusion by an increase in oxidative stress, infl ammation, apoptosis, and necrosis (Bonventre and Weinberg, 2003;Devarajan, 2006). MiR-21 down-regulated apoptosis and necrosis of renal TECs, which promoted cellular proliferation and played a protective role in the response to stress and infl ammation in renal IRI (Lindsay, 2008;Thum et al, 2008a;Godwin et al, 2010). As shown in a previous animal study, knockdown of miR-21 increased cell death.…”
Section: Mir-21 and Ischemia Reperfusion Injurymentioning
confidence: 68%
“…As shown in a previous animal study, knockdown of miR-21 increased cell death. However, a confl icting result was also noted in vitro: over-expression of miR-21 did not prevent cell death following simulated ischemia (Godwin et al, 2010). These results indicated the role of miR-21 is a two sided sword in renal IRI: neither under-nor over-expression led to adverse consequences (Fig.…”
Section: Mir-21 and Ischemia Reperfusion Injurymentioning
confidence: 84%
See 1 more Smart Citation
“…AKI microarray data also showed that several miRNAs (miR-21, miR-20a, miR-146a, miR-199a-3p, miR-214, miR-192, miR-187, miR-805, and miR-194) are differentially expressed. 26 These miRNAs are defined as the lymphocyte-independent signature of ischemic renal injury. However, in several tissues, including the kidneys, ATF3 acted as an early inducible transcriptional repressor 27 and inhibited lymphocytedependent ischemic renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs may be ideal candidates as biomarkers of disease [82][83][84][85][86]. Several factors (the relatively consistent changes seen in diseases, reliable analysis methods, tissue-specific expression patterns, less complexity than mRNAs, no post-processing modification, and amplifiable signals) contribute to making miRNAs ideal candidates, especially in the cancer diagnostic field [87][88][89][90][91].…”
Section: Biomarker Values Of Mirna In Xenotransplantationmentioning
confidence: 99%